Migration and nutrition - Joy Merrell (The New Dynamics of Ageing, 2018)
This chapter reports the findings from an ESRC funded project called MINA which was a three-year project that examined ageing, migration, and nutrition across two generations of Bangladeshi women living in Cardiff, UK and Sylhet, Bangladesh. Nutrition plays a key role in the health status of the Bangladeshi population as it does for the general population. However, there is a lack of knowledge regarding how eating patterns and migration affects this group’s nutritional status and experiences of ageing. The MINA project addressed these gaps using interdisciplinary approaches. Findings indicated that consumption of high fat, energy dense foods combined with low levels of physical activity led to high levels of obesity amongst Bangladeshi mothers an daughters living in Cardiff who also reported poorer health status than mothers and daughters residing in Bangladesh. A need for improved access to culturally appropriate leisure facilities as well as culturally sensitive health promotion and public health campaigns and resources was identified.